Glacitectonic rafts and their role in the generation of Quaternary subglacial bedforms and deposits. (November 2021) - Evans, David J. A.; Phillips, Emrys R.; Atkinson, Nigel
Abstract: Landforms and sediments on the palaeo–ice stream beds of central Alberta record glacitectonic raft production and subsequent progressive disaggregation and moulding, associated substrate ploughing, and grooving. We identify a subglacial temporal or developmental hierarchy that begins with incipient rafts, including en échelon hill-hole complexes, hill-hole pairs, and strike-slip raft complexes, all of which display patterns typical of transcurrent fault activation and pull apart. Many display jigsaw puzzle–style fragmentation, indicative of substrate displacement along shallow décollement zones and potentially related to patchy ice stream freeze-on. Their gradual fragmentation and smoothing produces ice flow-transverse ridges (ribbed moraine), hill-groove pairs, and paraxial ridge and groove associations. Initiator scarp and megafluting associations are indicative of raft dislodgement and groove ploughing, leading to the formation of murdlins, crag-and-tails, stoss-and-lee type flutings and drumlins, and Type 1 hogsback flutings. Downflow modification of rafts creates linear block trains (rubble stripes), stoss-and-lee type megaflutings, horned crag-and-tails, rubble drumlinoids, and murdlins, diagnostic of an immature palaeo–ice stream footprint. Lateral ice stream margin migration ingests disaggregated thrust masses to form ridged spindles, ladder-type morphologies, and narrow zones of ribbed terrain and Type 2 hogsback flutings, an assemblage diagnostic of ice stream shear margin moraine formation.